Synergy of Village Consultative Body and Village Head Toward Good Governance - Damar Amanu; Novi Sri Utami; Diyan Isnaeni (Academia Open, 2025)
General Background: Village governance plays a crucial role in Indonesia’s decentralization framework, serving as a foundation for democratization and local empowerment. Specific Background: Despite legal instruments such as Law Number 6 of 2014 and its amendment in Law Number 3 of 2024, challenges persist in harmonizing the relationship between the Village Consultative Body (BPD) and the Village Head. These challenges manifest in weak institutional synergy, limited transparency, and low community participation. Knowledge Gap: Previous studies have discussed administrative structures but rarely analyzed the juridical-sociological mechanisms necessary to optimize good governance at the village level. Aims: This study aims to examine how the BPD and Village Head can function synergistically within the framework of transparency, accountability, and participatory governance. Results: Findings reveal that effective collaboration depends on clearly defined authority boundaries, strengthened institutional capacity, and adherence to legal and ethical norms that promote transparency and accountability. Novelty: The study integrates normative juridical analysis with sociological interpretation, offering a model of village governance rooted in legal compliance and ethical partnership. Implications: Strengthening the synergy between the BPD and Village Head enhances local democracy, fosters community trust, and transforms village governance into a system that is transparent, accountable, and participatory Highlights: Strengthening synergy between BPD and Village Head ensures balanced authority and effective governance. Transparency and accountability serve as the ethical foundation for public trust and participation. Legal awareness and institutional capacity are vital for realizing sustainable village democracy. Keywords: Village Consultative Body, Village Head, Good Governance, Transparency, Accountability